Investigating an Erupting Metric-decimetric Radio Depression and Its Physical Origin - B. T. Wang; X. Cheng; J. Y. Yan; C. Xing; W. T. Fu; L. Wu; L. Deng; A. L. Lan; Y. Chen; C. Wang; M. D. Ding (The Astrophysical Journal)
We present direct metric-decimetric radio imaging observations of a fascinating quiescent filament eruption on 2024 March 17 using data from the DAocheng Radio Telescope, with a combination of the Solar Dynamics Observatory and the Chinese H α Solar Explorer. At the radio band, even though the filament is difficult to identify in its early phase, it rapidly became distinct and formed a continuous loop-like dark structure during the eruption, i.e., so-called radio depression. Compared with the fragmentation of the erupting filament observed at the H α and EUV bands, the radio depression appeared more coherently. Based on synthetic radio images from a three-dimensional magnetohydrodynamics simulation of a flux-rope-filament eruption, it is suggested that the radio depression originates from the absorption of cold and dense materials within the erupting flux rope to the background emission. The absorption seems to be stronger than that at the H α and EUV bands, thus leading to their apparent discrepancies. Moreover, the radio depression is also found to occupy the lower part but not the whole body of the flux rope.